The Influence of Interest in Learning Mathematics on the Ability to Solve Numeracy Problems Reviewed from the Self-Efficacy of Fifth Grade Elementary School Students in Cluster 29, Saradan District, Madiun Regency - Romdhiani, Ainin Meilia; Supianto, Supianto; Triyani, Septi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Numeracy is one of the important skills that students need to master at the basic education level. It aims to equip students with logical, analytical, systematic, critical and creative thinking as well as the ability to work together . However, many students still experience difficulties in solving numeracy problems. Based on observations made by researchers at SDN Bandungan 01, Saradan sub-district, 15 out of 25 students in class V still experienced difficulties in solving numeracy problems. The author is interested in conducting research on the effect of interest in learning mathematics on the ability to solve numeracy problems in terms of the self-efficacy of grade V students of elementary school se-gugus 29 Saradan Sub-district, Madiun Regency.The research knowing the significant influence between interest in learning mathematics on the ability to solve numeracy problems in terms of self-efficacy of grade V students of elementary school se-gugus 29 Saradan Sub-district, Madiun Regency. The use of the Systematic Literature Review (SLR) method by analyzing various relevant studies that discuss learning interest and numeracy problem-solving abilities in terms of self-efficacy. The research approach that will be carried out is a quantitative approach with a correlational method to identify the effect of student interest in learning on numeracy skills. In addition, several studies also concluded that self-efficacy influences students' interest in learning and numeracy problem-solving abilities.